CEA-Ki-67- Pathologic Subtype: An Adjunct Factor for Refining Prognosis in Stage I Pulmonary Adenocarcinoma - Yu, Dongzhi; Sun, Yanbin; McNutt, Michael A.; Xu, Shun (Frontiers in Surgery, 2022)
Objectives: The prognosis for stage I pulmonary adenocarcinoma is generally good, however some stage I patients have an unexpectedly poor outcome. This warrants consideration of adjunct markers. In this study we analyze carcinoembryonic antigen, Ki-67, and pathologic subtype in combination for prognostic evaluation of stage I pulmonary adenocarcinoma. These factors were selected for study as they have been shown to be individually associated with prognosis in many studies. Methods: A total of 650 patients with stage I pulmonary adenocarcinoma were investigated retrospectively. Each patient was re-staged using standard TNM criteria. CEA values were obtained from preoperative blood samples, and Ki-67 was evaluated with tumor tissue immunohistochemistry. Patient clinicopathologic characteristics, survival status, and date of death were obtained from medical records and telephone follow-up. Results: CEA>4.4ng/ml, Ki-67>13%, and a solid-micropapillary tumor growth pattern were each independent adverse prognostic markers for 5-year disease specific survival in stage I pulmonary adenocarcinoma. However, in combination these 3 factors yielded a prognostic value (designated “CEA-Ki-67-pathologic subtype” value). Stage I pulmonary adenocarcinoma of low-risk CKP value show biologic behavior similar to TNM stage IA1 tumors, while stage I tumors of high-risk CKP value are similar in prognosis to TNM stage II. Conclusion: The CKP value may be used as an adjunct to the TNM classification, which may yield a more accurately defined prognosis for cases of stage I pulmonary adenocarcinoma. CKP value may identify patients at higher risk who may benefit from adjuvant chemotherapy. Conversely lower risk CKP values may support avoidance of chemotherapy.